2021
DOI: 10.3390/cells10020473
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Mitochondrial Homeostasis by sAC-Derived cAMP Pool: Basic and Translational Aspects

Abstract: In contrast to the traditional view of mitochondria being solely a source of cellular energy, e.g., the “powerhouse” of the cell, mitochondria are now known to be key regulators of numerous cellular processes. Accordingly, disturbance of mitochondrial homeostasis is a basic mechanism in several pathologies. Emerging data demonstrate that 3′–5′-yclic adenosine monophosphate (cAMP) signalling plays a key role in mitochondrial biology and homeostasis. Mitochondria are equipped with an endogenous cAMP synthesis sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 102 publications
0
12
0
Order By: Relevance
“…Numerous studies argue for the key role of the cAMP signaling in mitochondrial biology and homeostasis [ 72 , 73 ]. However, only a few reports have linked cAMP signaling to the regulation of mitochondrial homeostasis by AMPK.…”
Section: Functional and Translational Significance Of The Camp/ampk Axismentioning
confidence: 99%
“…Numerous studies argue for the key role of the cAMP signaling in mitochondrial biology and homeostasis [ 72 , 73 ]. However, only a few reports have linked cAMP signaling to the regulation of mitochondrial homeostasis by AMPK.…”
Section: Functional and Translational Significance Of The Camp/ampk Axismentioning
confidence: 99%
“…It has been suggested that sAC, as an intracellular pH and metabolic sensor, may play role in a tumorigenesis, since cellular pH and metabolism strongly correlate to tumor proliferation and metastatic spread [ 117 ] Studies have shown that sAC expression is diminished in many solid and hematologic human cancers, including embryonic carcinoma, teratoma, seminoma, yolk sac tumor, some types of leukemia, and others [ 118 ]. Preliminary data on animal and cell line models demonstrated that loss of sAC activity enhances cellular transformation in vitro, activates the MAP kinase signaling pathway, and induces tumorigenesis [ 118 , 119 ]. However, to our knowledge, reports regarding sAC involvement in OC development are missing.…”
Section: Signal Transduction Pathways As Potential Therapeutic Targetsmentioning
confidence: 99%
“…Impairment of OXPHOS dysfunction is linked to patients with primary open-angle glaucoma 31 and there is supporting evidence indicating that OXPHOS serves as the primary location for the production of mitochondrial superoxide in the presence of PQ 19 . Because the sAC/cAMP pathway is associated with mitochondrial biogenesis and OXPHOS function 10, 12, 32, 33, 34 , we next examined whether sAC activation promotes expression levels of PGC-1α and mitochondrial transcription factor A (TFAM) proteins, and OXPHOS complexes in the retina affected by oxidative stress. We found that oxidative stress significantly decreased PGC-1α and TFAM protein expression in the retina (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, our findings emphasize a critical role of the sAC/cAMP/PKA signaling axis in mitochondrial protection in RGCs. Activation of cAMP signaling is crucial in mitochondrial biogenesis in mammalian cells 40, 50 and a deficiency of sAC has been linked to impaired OXPHOS activity 12 . Hence, our findings suggest that the sAC/cAMP/PKA-mediated modulation of mitochondrial biogenesis could protect RGCs by enhancing OXPHOS activity in response to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation